'Inverse association between the total naevus count and melanoma thickness'. (27th April 2020) - Marghoob, N.G.; Liopyris, K.; Navarrete‐Dechent, C.; Dusza, S.W.; Balais, G.; Megaris, A.; Papageorgiou, C.; Apalla, Z.; Lallas, A.
Abstract: Background: Individuals with a high total naevus count (TNC) are at a higher risk to develop melanoma, and screening efforts have been largely focused on this group. However, some studies suggest that melanomas of patients with many nevi are thinner than those of patients with few nevi. Additionally, nodular melanoma has been associated with individuals with a low naevus count. Objective: To investigate the association between TNC and melanoma Breslow thickness. Methods: A two‐centre retrospective study from 1 January 2016 to 1 January 2018. This included three hundred and twenty‐six consecutive melanoma patients from two tertiary melanoma centres. The mean age at presentation was 58.3 years (SD = 15.9), and the majority (54.9%, N = 179) were men. Incidence of new in situ and invasive melanomas and correlation with TNC were measured. Results: The mean total naevus count for patients presenting with in situ melanoma was 57.2 (range 4–178), while for patients presenting with invasive disease was 31.5 ( P = 0.01). In situ disease was associated with a higher TNC across all ages. For invasive melanoma, a positive association between age and Breslow thickness was observed, while TNC was inversely associated with Breslow thickness. Each additional naevus accounted for a 4% decreased likelihood that the subject had invasive disease. Conclusion: Patients with a higher naevus count had thinner melanomas and more melanomas in situ, independent of age and sex.